1980
DOI: 10.1007/bf00343612
|View full text |Cite
|
Sign up to set email alerts
|

Classification of organic brain syndromes by cluster analysis

Abstract: Cluster analysis was carried out on a sample of 92 patients with behavior disorders caused by degenerative, vascular, (alcohol) toxic, and other diseases of the brain. Rating variables of the AMDP system concerning mental state, social behavior, need for special care, sleep disorders, autonomic, physical, and neurologic symptoms were used in the absence of severe degrees of disordered consciousness such as stupor, coma, delirium tremens, and gross cerebral lesions. Results suggested the existence of four major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The recorded documented data with the AMDP-rating scale system were prepared by principal and discriminant function analysis to form cluster derived groupings of patients with organic brain syndromes to correlate them with the results of cerebral rates of oxygen, glucose, and lactate (Krüger & Haubitz, 1980). The sample had to be divided on the base of clinical signs and symptoms in degenerative, vascular, alcohol toxic and other etiologies.…”
Section: Psychopathologymentioning
confidence: 99%
“…The recorded documented data with the AMDP-rating scale system were prepared by principal and discriminant function analysis to form cluster derived groupings of patients with organic brain syndromes to correlate them with the results of cerebral rates of oxygen, glucose, and lactate (Krüger & Haubitz, 1980). The sample had to be divided on the base of clinical signs and symptoms in degenerative, vascular, alcohol toxic and other etiologies.…”
Section: Psychopathologymentioning
confidence: 99%
“…Other popular methods for extracting groups or syndromes such as cluster analysis are seen less frequently [e.g. 1,27,38]. In the study by Sato et al [38], in which the authors identified phenomenological subtypes of acute mania, cluster analysis was combined with factor analysis, but in a sequential manner.…”
Section: Introductionmentioning
confidence: 98%